Nasolabial bilateral cyst as cause of the nasal obstruction: Case report and literature review - Enoki, Alexandre Minoru; Pizarro, Gilberto Ulson; Morais, Marcelo de Sampaio; Fernandes, Danilo Pereira Pimentel; Oliveira, Paulo Roberto Grimaldi (Arquivos Internacionais de Otorrinolaringologia, 2012)
Introduction: The nasolabial cyst is a rare disease, usually unilateral, benign, of embryonic origin, located in soft parts from the nasolabial folds and nasal wings. The diagnosis is essentially clinic, take into consideration the cyst topography, that is usually asymptomatic.Objective: This article has as main goal the description of a unusual case of nasolabial bilateral cyst with nasal obstruction, its treatment, anatomic pathological and accompaniment, besides the literature review.Case Report: Female patient, brown, 24 years old, showing bulging in nasolabial region and nasal obstruction. Physical and complementary exams with nasolabial cyst. Indicate surgical treatment of excision of the lesion.Final Considerations: The nasolabial bilateral cyst, although is rare, is a possible cause for the nasal obstruction, with good response to surgical therapy.
Keywords: not odontogenic cyst; nasal obstruction; cysts